2020
DOI: 10.1029/2020gh000272
|View full text |Cite
|
Sign up to set email alerts
|

The Silver Lining of COVID‐19: Estimation of Short‐Term Health Impacts Due to Lockdown in the Yangtze River Delta Region, China

Abstract: The outbreak of COVID-19 in China has led to massive lockdowns in order to reduce the spread of the epidemic and control human-to-human transmission. Subsequent reductions in various anthropogenic activities have led to improved air quality during the lockdown. In this study, we apply a widely used exposure-response function to estimate the short-term health impacts associated with PM 2.5 changes over the Yangtze River Delta (YRD) region due to COVID-19 lockdown. Concentrations of PM 2.5 during lockdown period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
(30 reference statements)
0
32
0
Order By: Relevance
“…The substantial improvements in air quality since the lockdown may have brought down 51.3 thousand premature deaths and 1066.8 thousand YLLs in China, and most benefits were obtained in the four key regions. Three previous studies have estimated the health impacts from air pollution changes during COVID-19 lockdown in China ( Huang et al, 2020 ; Chen et al, 2020b ; Giani et al, 2020 ). Huang et al observed that the PM 2.5 reduction during the lockdown was associated with 42.4 thousand less premature deaths over the Yangtze River Delta region, China ( Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The substantial improvements in air quality since the lockdown may have brought down 51.3 thousand premature deaths and 1066.8 thousand YLLs in China, and most benefits were obtained in the four key regions. Three previous studies have estimated the health impacts from air pollution changes during COVID-19 lockdown in China ( Huang et al, 2020 ; Chen et al, 2020b ; Giani et al, 2020 ). Huang et al observed that the PM 2.5 reduction during the lockdown was associated with 42.4 thousand less premature deaths over the Yangtze River Delta region, China ( Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The log-linear exposure-response function below was applied to estimate the short-term health impacts attributable to the changes in PM 2.5 and O 3 ( Huang et al, 2020 ; Liu et al, 2018 ). Where Y d denotes the daily number of deaths in each province avoided by the air quality improvement; y 0 represents the daily mean total and cause-specific (CVD and RESP) mortality rate (/100,000); β 0 is the regression coefficient derived from the RRs associated with every 1 μg/m 3 change in PM 2.5 and O 3 ; x 1 indicates daily mean air pollutant concentration in 2020; x 0 means daily mean air pollutant concentration in the same calendar in 2018–2019; Pop denotes the total population size in each province; d donates the number of days in a period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While great efforts in recent years have been made to reduce air pollution in particularly fine particulate matter (PM 2.5 ) concentration, China is still suffering relatively heavy air pollution and potentially high health risks particularly in densely populated regions ( Nie et al 2018 ; Sahu et al 2020 ; Shen et al 2017 ; Shen et al 2020 ). Haze events still occurred due to that enhanced production of secondary aerosol components might compensate the reduced primary emissions ( Chang et al 2020 ; Huang et al 2020b ; Le et al 2020 ; Sun et al 2020 ; Wang et al 2020a ), yet an overall improvement of air quality was very probably during COVID-19 period ( Bao and Zhang 2020 ; Huang et al 2020a ; Shi and Brasseur 2020 ; Xu et al 2020b ). In what extent this improvement influences the health burden, and how large is the economic cost associated with the change of air quality during COVID-19 pandemic?…”
Section: Introductionmentioning
confidence: 99%
“…The preoccupation with outdoor air pollution (Huang et al, 2020b) may have distorted our views of how exposure might have changed. This is an especially distinct period when people spent so…”
Section: Accepted Manuscriptmentioning
confidence: 99%